Description of four new species of the genus Ptilocerembia Friederichs, 1923 (Embioptera: Ptilocerembiidae) from Thailand - Poolprasert, Pisit; Edgerly, Janice S. (Zootaxa, 2014)
Four new species of webspinners in the genus Ptilocerembia Friederichs (Ptilocerembiidae) are described including Ptilocerembia thaidina sp. n., P. senathami sp. n., P. catherinae sp. n. and P.  rossi sp. n. . from Thailand. Illustrations of heads, genitalia and papilla of adult males, sternite pattern of adult females together with photographs of adult males, females and their galleries for each species are provided. Notes on field observations and egg mass structure are given for P. catherinae sp. n. A distribution map and a dichotomous key to the Thai species in the genus Ptilocerembia are also included.